Warped product CR-submanifolds of LP-cosymplectic manifolds - Uddin, Siraj (Faculty of Sciences and Mathematics, University of Nis, 2010)
In this paper, we study warped product CR-submanifolds of LP-cosymplectic manifolds. We have shown that the warped product of the type M = N(T) x (f)N(perpendicular to) does not exist, where N(T) and N(perpendicular to) are invariant and anti-invariant sub-manifolds of an LP-cosymplectic manifold (M) over bar , respectively. Also, we have obtained a characterization result for a CR-submanifold to be locally a CR-warped product.